2004
DOI: 10.5897/ajb2004.000-2088
|View full text |Cite
|
Sign up to set email alerts
|

Saccharification of banana agro-waste by cellulolytic enzymes

Abstract: Banana is major cash crop of this region generating vast agricultural waste after harvest. The agrowaste including dried leaves and psuedostem after harvest was used as substrate for the release of sugars. Saccharification of banana agro waste by cellulases of Trichoderma lignorum was investigated. The steam treated agro-waste yielded 1.34 mg/ml of reducing sugars after 24 hr. The size of substrate affected saccharification where the smaller size (<120 µ) yield more sugars. Maximum sugars were released at pH 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The saccharification percentage was evaluated by Eq. 1 (Baig et al 2004), Saccharification (%) = Xylose (mg/mL) / substrate (mg/mL) × 100…”
Section: Saccharification Of Biomass Wastesmentioning
confidence: 99%
“…The saccharification percentage was evaluated by Eq. 1 (Baig et al 2004), Saccharification (%) = Xylose (mg/mL) / substrate (mg/mL) × 100…”
Section: Saccharification Of Biomass Wastesmentioning
confidence: 99%
“…The maximum production of FPase 1.01 U mL -1 , CMCase (2.69 U mL -1 ), b-glucosidase (0.82 U mL -1 ) and xylanase (82.99 U mL -1 ) by Trichoderma atrovirideAD-130 was observed at 30°C. Further increase in incubation temperature from 30 to 33°C or above resulted in decreased cellulase and xylanase production.Contrary to the above results, different cellulolytic fungi were found to produce maximum cellulases at 28°C, for example, T. Viride (Zhou et al, 2008), T. Harzianum (Ahmad Idi and Mohamad S. Eva (2011), T. Asperullum (Chen Y et al, 2010) and A. niger (Harun M.Y et al,2011) yielded maximum cellulases at 28°C.On the other hand, Baig et al (2004) reported maximum cellulases production by T. Reesei at 30°C while (Ahamed, A., and Vermette, P 2008) found maximum cellulases and xylanase activity by Aspergillus fumigates at 30°C. However, as many researchers had reported on variety of optimum temperatures, it could be suggested that the optimal condition for cellulases production depended not only upon the variation of the microorganism (Sukhang et al, 2020) but also the temperature variation of the culture conditions.…”
Section: Effect Of Incubation Period On Enzyme Production Of Trichode...mentioning
confidence: 87%
“…Every 2 h, the reaction mixture was withdrawn, centrifuged at RCF of 2350 g at 4 °C for 15 min, and the supernatants were used for the quantification of the reducing sugar content by the 3,5-dinitrosalicylic acid method using xylose as a standard. The saccharification percentage was calculated by the equation given by Baig et al (2004), which is shown below (Eq. 2):…”
Section: Application Of Xylanase In the Hydrolysis Of Agro-residuesmentioning
confidence: 99%